ANALISIS SISTEM INFORMASI AKUNTANSI ATAS PEMBERIAN KREDIT PADA PD. BPR BKK KABUPATEN PEKALONGAN - Syahrul Muthoharroh, 0835030725; Kartika, Andi (Students Journal of Accounting and Banking, 2014)
System aims to give easy credit application process for its customers. This research is a system that analyzes credit accounting informaasi contained in PD. BPR BKK Pekalongan. Data collection methods used in this study were interviews, observation and documentation. The analytical tool used in this study is a flowchart (flowchart) through the procedure images. Ie by evaluating the organizational structure, identify the accounting information system of credit provision, identify existing weaknesses and suggest improvements. Based on the analysis of the data found that the organizational structure of the image depicted is one that can lead to wrong interpretation. To the credit has the task and the dual function which may result in data manipulation and collusion. Documents that are used most of the already printed serial number that its use should be accounted for by the authorities. List Bills Employees should not only be signed by the Treasurer credit alone but by the relevant agencies, Teller and Leadership. Recordation system already uses that generate accrual basis financial statements more reliable, more accurate, comprehensive and relevant for decision making.Keywords: Credit, Accounting Information Systems, Internal Control